The population status and threats of Taxus cuspidata, a plant species with extremely small populations in China - Ting Long; Xinlei Wu; Yin Wang; Jie Chen; Chao Xu; Jingwen Li; Junqing Li; Runguo Zang (Global Ecology and Conservation, 2021)
Taxus cuspidata Siebold et Zuccarini, one of the plant species with extremely small populations in China, is listed as a first-class national key protected wild plant that urgently needs to be rescued. However, there are different viewpoints on the population status of T. cuspidata. To elucidate the current actual population status of T. cuspidata, we conducted a systematic field survey in the distribution area of T. cuspidata in China, and analyzed the size structure, sex ratio, dynamics, and threat factors of T. cuspidata populations. Our results are as follows. (1) T. cuspidata was mainly distributed in Wangqing County, Helong City, Hunchun City of Jilin Province, and Muling City of Heilongjiang Province, while seldom distributed in Liaoning Province. T. cuspidata was distributed in the broad-leaved-conifer-Korean pine mixed forest in Northeast China, mostly as sporadic single individuals or scattered small populations. The highest density of adult individuals of T. cuspidata was 20 individuals/0.1 ha in DHZ, and the highest density of regeneration individuals was 28 individuals/0.1 ha in JGL. There was a significant exponential relationship (p < 0.05) and a serious polarization between the number of adult and regeneration individuals. (2) The T. cuspidata population showed an inverted J-shaped size structure, and its survival curve belonged to the Deevey Ⅲ, in which the number of surviving individuals decreased sharply from the sapling to the seventh size class. The ratio of females to males in the T. cuspidata population was 1:2.30, which was significantly different from 1:1 (p < 0.001). (3) Disturbance intensity was the primary environmental variable affecting the regeneration and adult individuals of T. cuspidata. Interestingly, disturbance factors together with habitat factors explained 41.6% and 59.8% of the variation in the number of regeneration and adult individuals respectively, and habitat factors (29.6%) had a greater independent effect than disturbance factors (17.3%) on regeneration individuals, whereas disturbance factors (16.0%) had a greater independent effect than habitat factors (12.5%) on adult individuals. Taken together, we highlighted that excessive disturbance directly resulted in the sharp decline in the population size and habitat area of T. cuspidata in China. Currently, T. cuspidata is endangered and faced with a high risk of local extinction in China. Therefore, we should continue to pay more attention to this species and we suggest that the International Union for Conservation of Nature (IUCN) could reconsider the threatened category of T. cuspidata.